What Coast: resort or resource? - Susana Lobo (Anuari d’Arquitectura i Societat)
Between land and sea, the coast is one of the most extraordinary and unique habitats occupied by man. On this threshold, dune landscapes are particular sensitive environments, in constant movement and transformation. Conservation measures have been implemented to regulate intervention on such sites, mainly concerning the safeguarding of primary dunes, but little consideration has been given to the in-depth structure of these ecosystems. With the pressure of seaside tourism development, the remaining untouched dune areas are facing serious threat. In Portugal, many have recently lost their classification as part of the National Ecologic Reserve (REN), since 2006 defined by proposal of each municipality. Grândola, in the district of Setúbal, is at the center of present environmental concerns, with 7 new mega luxury resorts predicted for the Tróia Peninsula and Comporta’s seafront, 4 of them partially on primary dune and 4 comprising the construction of extensive golf courses. Towards the United Nations 2030 Sustainable Development Goals (SDGs), the focus should be on protecting the existing biodiversity, as part of the Natura 2000 network, and promoting the balanced use of local natural resources, in particular in an area of severe water shortage. That is the true luxury: to foster resource, not resorts.